PENGARUH KONSERVATISME, KOMPENSASI MANAJEMEN, DAN FAKTOR LAINNYA TERHADAP PENGHINDARAN PAJAK - YESHINTA CHAMAS; HILARY FLORA A. T. LASAR (E-Jurnal Manajemen Trisakti School of Management (TSM), 2026)
This research examines the determinants of corporate tax avoidance by analyzing the roles of leverage, profitability, independent board of commissioners, audit committee, capital intensity, firm size, accounting conservatism, and management compensation. The study focuses on 110 manufacturing companies listed on the Indonesia Stock Exchange during the 2022 to 2024 observation period. Sample selection was conducted using a purposive sampling approach. Secondary data were analyzed using multiple linear regression techniques. The findings reveal that profitability, audit committee, and firm size show a significant impact on corporate tax avoidance. In contrast, leverage, independent board of commissioners, capital intensity, accounting conservatism, and management compensation do not significantly influence tax avoidance practices.